How bacteria overcome flagellin pattern recognition in plants. (June 2022) - Sanguankiattichai, Nattapong; Buscaill, Pierre; Preston, Gail M.
Abstract: Efficient plant immune responses depend on the ability to recognise an invading microbe. The 22-amino acids in the N-terminal domain and the 28-amino acids in the central region of the bacterial flagellin, called flg22 and flgII-28, respectively, are important elicitors of plant immunity. Plant immunity is activated after flg22 or flgII-28 recognition by the plant transmembrane receptors FLS2 or FLS3, respectively. There is strong selective pressure on many plant pathogenic and endophytic bacteria to overcome flagellin-triggered immunity. Here we provide an overview of recent developments in our understanding of the evasion and suppression of flagellin pattern recognition by plant-associated bacteria. Graphical abstract: Image 1 Highlights: Flagellin-triggered immunity relies on functional pattern recognition receptors (PRRs) and their interactors. Bacteria subvert flagellin-triggered immunity before and after flagellin-derived PAMP recognition. Bacteria manipulate flagellin synthesis, structure and degradation to impair PRR activation. Bacteria secrete extracellular and intracellular effectors to suppress flagellin-triggered immune responses.